INTENTION TO CONTINUE PARTICIPATING: SYSTEM INTERACTIVITY, VIRTUAL SITES, COMMUNITY COMMITMENT IN ONLINE HIJABS COMMUNITY - Untarini, Nindria; Teofilus, Teofilus; Sutrisno, Timotius F.C.W (Jurnal Aplikasi Manajemen, 2021)
This study aims to examine system interactivity affecting member commitment and intention to continue participating in the online hijabs community. At the same time, testing how the role of virtual sites in the form of posting in strengthening the relationship (moderate) system interactivity to continue to participate in the online hijabs community. An online hijabs community was researched because the problem observed in the research was relevant to the virtual community. Based on 358 valid responses from students in Surabaya who actively joined the online hijabs community obtained from questionnaires at each university in Surabaya, structural equations modeling (SEM) was used to test the research model. The results show that system interactivity affects commitment to the community, but does not affect the intentions of members to continue their participation in online hijabs communities. Likewise, commitment to the community does not stimulate the intentions of members to remain actively participating in online hijabs communities. Although, an interesting form of posting can strengthen the system's interactivity relationship of members' intentions to continue their participation in online communities. Implications for both marketing theory and practice, limitations, and future research on video storytelling in social media are discussed.